2021
DOI: 10.1111/eci.13496
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoids for acute respiratory distress syndrome: A systematic review with meta‐analysis and trial sequential analysis

Abstract: BACKGROUNDAcute respiratory distress syndrome (ARDS) is an acute progressive respiratory failure characterized by pulmonary oedema, hyaline membrane formation and atelectasis secondary to a variety of lung diseases or extrapulmonary events, such as severe pneumonia, drowning, septic shock and severe acute pancreatitis (SAP). ARDS is one of the common critical diseases in intensive care unit (ICU). According to a large global observational study (LUNG SAFE), 1 the morbidity

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 45 publications
1
7
0
Order By: Relevance
“…Glucocorticoids have a potent effect and can indirectly play a role by inhibiting the activation of inflammatory processes, including inhibiting the gene transcription of proinflammatory factors, inhibiting the expression of inducible nitric oxide, and promoting the production of interleukin-10 and interleukin-4 [ 25 ]. In addition, glucocorticoids can also improve coagulation and inhibition response, thereby normalizing the ventilation/blood flow ratio [ 26 ]. Based on the abovementioned effects of hormones, they should theoretically significantly improve the oxygenation index in ARDS patients, but the clinical results are inconsistent.…”
Section: Discussionmentioning
confidence: 99%
“…Glucocorticoids have a potent effect and can indirectly play a role by inhibiting the activation of inflammatory processes, including inhibiting the gene transcription of proinflammatory factors, inhibiting the expression of inducible nitric oxide, and promoting the production of interleukin-10 and interleukin-4 [ 25 ]. In addition, glucocorticoids can also improve coagulation and inhibition response, thereby normalizing the ventilation/blood flow ratio [ 26 ]. Based on the abovementioned effects of hormones, they should theoretically significantly improve the oxygenation index in ARDS patients, but the clinical results are inconsistent.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, timely inhaled corticosteroids and beta-2 agonists may slow the progression by reducing lung inflammation and enhancing alveolar fluid clearance in ARDS patients (29). Only single-center study and small randomized trial demonstrated a certain effect of different dose of glucocorticoids in ARDS (5,30). In our case, low-dose prednisone acetate played an important role in the treatment of waterproofing spray-related ARDS.…”
Section: Discussionmentioning
confidence: 61%
“…We stopped anti-infective therapy after mNGS test, on account of lacking of etiological evidence. The recommendations from evidence-based medicine point out that a low dose of methylprednisolone 0.5-1 mg/kg body weight/d for mild ARDS (5). The total dosages of methylprednisolone were calculated based on the bodyweight of the patient (54 kg).…”
Section: Case Presentationmentioning
confidence: 99%
See 1 more Smart Citation
“…Metanalyses in patients with severe sepsis or septic shock have reported a significant reduction in all-cause mortality, reduced incidence of MODS, and reduced duration of mechanical ventilation with ulinastatin and with a combination of thymosin alpha-1 (Tα1) and ulinastatin [9,10]. In patients with ARDS, the use of agents such as steroids [11,12] and ulinastatin [13] has been shown to reduce mortality and duration of mechanical ventilation significantly. Although some reports suggested possible benefits in terms of reduced length of hospital stay, the need for surgical intervention, and the mortality rate with the use of steroid therapy in severe AP [14], the role of steroids in AP is controversial.…”
Section: Introductionmentioning
confidence: 99%